Abundance, Fishing Season and Management Strategy for Blue Swimming Crab (Portunus pelagicus) in Pangkajene Kepulauan, South Sulawesi, Indonesia - Eko Sri Wiyono; Ihsan (Tropical Life Sciences Research, 2018)
In order to manage blue swimming crabs in Pangkajene Kepulauan, management measures are required. Since the environment which affects the abundance of the blue swimming crab varies seasonally, it is necessary to take into account the seasonal nature with the aim of developing a management strategy. The objectives of this study are to define the abundance of and fishing season of blue swimming crabs in the Pangkajene Kepulauan waters, South Sulawesi, Indonesia. The fishing season was analysed using seasonal index analysis, while fish abundance was analysed by means of Equilibrium-Schaefer. The result of this study demonstrated that fishermen allocate their fishing gear all year, although the fish catch is seasonal. Based on analysis of the result, the fishing season for the blue swimming crabs is short. The peak fishing season starts in May and finishes in June. However, in order to enable their families to earn a living, fishermen operated their fishing gear throughout the year. As a result, both catch landing and effort were close to maximum sustainable yield (MSY). In order to reduce fishing pressure, it is necessary to reduce fishing gear and have a seasonal arrangement regarding fishing gear allocation.